Allergy-Related Disorders in the Construction Industry. (5th December 2013) - Carino, Mauro; Romita, Paolo; Foti, Caterina
Abstract : Working conditions in the construction industry have improved in many industrialized countries, but heavy physical work with recurrent exposure to chemical agents, dust, and climatic influences still represents considerable risk for construction workers and may affect their health. The aim of this review is to analyze available data of the literature on allergy-related respiratory and skin disorders with emphasis on a preventive appraisal in order to produce statements and recommendations based on research evidence. The most common agents involved in the construction industry as a cause of occupational asthma (OA) in industrialized countries are isocyanates, wood dust, resins, glues, cobalt, and chromium. Allergic contact dermatitis (ACD) is an immunologic cell-mediated response to a sensitizing agent and the most common sensitizing agents associated with construction workers are epoxy resins, thiurams and thiazoles, and chromates. Medical surveillance must consider individual risk factors such as differences in individual susceptibility and sensitization to agents at workplace. Once work-related disorder is confirmed, adequate fitness for work should be assessed for the worker impaired by health condition. A reliable diagnosis of an index case is a sentinel event that may reveal risks for workers with similar exposure, leading to a revised risk assessment at the workplace that should reduce the risk and prevent further cases.